The Impact of Instagram Social Media Information on the Transformation of Student Identity in Yogyakarta City - Afrilya Moudy Wuna; Dani Fadillah (Universitas Ahmad Dahlan, 2025)
This study aims to analyze how exposure to information about beauty on Instagram influences the identity transformation of female students at private universities in Yogyakarta. 's discussion focuses on three main aspects,namely: the process of forming a digital identity that is carried out selectively and aesthetically; the role of social validation in shaping self-confidence and self-assessment; and the discrepancy between digital identity and real identity that causes psychological pressure. The research uses a descriptive qualitative approach with data collectio techniques through online open questionnaires to ten informants who actively use Instagram and are exposed to beauty content. The analysis was conducted using Goffman's dramaturgy theory, Uses and Gratifications (U&G), and Social Identity Theory (SIT) to understand performative identity practices, social gratification needs, and social comparison processes in the digital space. The results show that female students construct digital identities as ideal images in an effort to gain positive impressions from their audience, but this creates a gap between their online representation and their authentic selves. The study confirms that Instagram functions as a complex space for identity negotiation and highlights the importance of digital literacy and reflective awareness in the use of social media among students.